The experiences and perceptions of 6 NGO leaders on the role and value of formal and informal learning in leadership continuity in the NGO sector across 3 historical periods in South Africa - Julie, Frank Joseph (School of Education, 2015)
Includes bibliographical references (leaves 87-92).